The Relation Between Television Viewing Time and Reading Achievement in Elementary School Children: A Test of Substitution and Inhibition Hypotheses - Supper, Wilfried; Guay, Frédéric; Talbot, Denis (Frontiers in Psychology, 2021)
Research has focused on the relations between television (TV) viewing time and children’s reading achievement. Two hypotheses have been proposed to explain this relation. The substitution hypothesis proposes that TV viewing distracts students from activities that are important for their learning. The inhibition hypothesis proposes that watching television inhibits important affective/cognitive skills. In this study, we test both hypotheses by estimating the relation between TV viewing time and reading achievement. We use the frequency of students’ leisure reading and the frequency of interactions between students and their parents as potential mediators to test the substitution hypothesis, whereas for the inhibition one, we use students’ intrinsic motivation to read and their level of inattention. Data come from the Québec Longitudinal Study of Child Development (QLSCD). Designed by the Institut de la statistique du Québec, QLSCD covers a wide range of themes. The QLSCD is representative of children in Québec and contains 2223 participants who were followed from 0 to 21 years old. The four structural models tested are built as follows: the TV viewing time at 6 years old predicts the four mediating variables at 8 years old, which in turn predicts reading achievement at 10 years old. In addition, we have tested models’ gender invariance. Results indicate that TV viewing time is not directly or indirectly associated with reading achievement. Specifically, it is not associated with the mediating variables of child-parent interactions, intrinsic motivation, and inattention. However, the frequency of leisure reading is negatively associated with the time spent watching TV. This association is very small (−0.07) and has no indirect effect on reading achievement. Finally, results do not vary according to the gender of the participants. Our results are in line with those of previous studies in the field and cast some doubts on the potential negative effects of TV viewing time on reading achievement.